Gravitational spin-orbit interaction: criteria of increase - Plyatsko, R. (Condensed Matter Physics, 1998)
The gravitational spin-orbit interaction in the region of the ultrarelativistic
orbital velocity of a spinning test particle in the Schwarzschild field is investigated
on the basis of the Mathisson-Papapetrou equations. Different
indications of an essential increase of this interaction, when the tangential
velocity becomes ultrarelativistic, are analysed. The main factor of growth
is the square of the relativistic Lorentz y-factor. Numerical estimations for
a high-energy electron in its path near the Earth’s surface and near a neutron
star are given. It is stressed that the widely recognised assumption
that the deviation of a spinning test particle from the geodesic trajectory is
caused by tidal forces is not correct. The real reason for this deviation is
the gravitational spin-orbit interaction. На основі рівнянь Матісона-Папапетру досліджено ґравітаційну спінорбітальну взаємодію в ультрарелятивістичному діапазоні орбітальної швидкості пробної частинки зі спіном у полі Шварцшільда. Проаналізовано різні ознаки суттєвого зростання цієї взаємодії, коли
танґенціяльна швидкість стає ультрарелятивістичною. Основним
фактором росту є квадрат релятивістичного y-фактора Лоренца.
Наведено числові оцінки для високоенергетичного електрона біля
поверхні Землі і нейтронної зорі. Підкреслено, що широко розповсюджене припущення про припливні сили як причину відхилення пробної частинки зі спіном від геодезійної траєкторії є некоректним.
Справжньою причиною такого відхилення є ґравітаційна спін—орбітальна взаємодія.